Effect of a 1‐year short message service in detoxified alcohol‐dependent patients: a multi‐center, open‐label randomized controlled trial. (27th December 2020) - Lucht, Michael; Quellmalz, Anne; Mende, Meinhard; Broda, Anja; Schmiedeknecht, Anett; Brosteanu, Oana; Höppner‐Buchmann, Jacqueline; Langosch, Jens; Stuppe, Markus; Schomerus, Georg; Klauer, Thomas; Grabe, Hans J.; et al.
Abstract: Background and Aims: Existing evidence suggests that text message interventions can help people to reduce their alcohol consumption. However, studies with alcohol‐dependent patients are lacking. In this study a 1‐year automatic mobile phone‐based short messaging service (SMS) intervention on alcohol consumption in patients after alcohol detoxification in hospital was compared with treatment as usual. Design: Multi‐center, randomized, controlled, two parallel‐group, observer‐blinded trial. Setting and Participants: Primary and secondary care: four hospitals and community (1 million residents, 7600 km 2 area in Germany). A total of 462 patients with alcohol dependence (ICD‐10) were included during inpatient detoxification treatment. Patients were randomly assigned (1 : 1) to an SMS intervention and treatment as usual (SMS + TAU; n = 230; mean age: 45.4 years; 22.6% women) or TAU alone ( n = 232 mean age: 44.5 years; 22.8% women). Planned, automated messages were sent to patients over 1 year to record assistance needs. A 'yes' or missing response triggered a telephone call from a hospital therapist. Outcome was assessed by an independent survey center. Measurements: The primary end‐point was a three‐category alcohol consumption measure covering months 10–12 after discharge: abstinence, non‐heavy drinking, heavy drinking [men > 60 g/day; women > 40 g/day equal to World Health Organization (WHO) criteria: high risk and very high risk, mean consumption]. Secondary end‐points were number of abstinent days over 12 months and frequency of abstinence. Results: The arms differed primarily in the heavy drinking category (intervention group 22.2%, TAU‐only group 32.3%) in months 9–12. This is reflected by an odds ratio (OR) = 1.68, 95% confidence interval (CI) = 1.11–2.54, P = 0.015 for heavy drinking versus non‐heavy drinking/abstinence. No difference between treatments was found with respect to any drinking versus abstinence (OR = 1.13). These results were confirmed by models adjusting for randomization strata. Conclusions: In Germany, a 12‐month mobile phone short messaging service‐based intervention enhanced the reduction in heavy drinking for 1 year in routine care among adults with alcohol dependence discharged from inpatient alcohol detoxification.